Design of Coaxial Resonator Bandpass Filter - Parameswaran, Kishok Kumaar (2018)
The purpose of this project is to design a coaxial resonator bandpass filter by connecting two dual mode resonators in parallel. This is called the parallel connected topology method. Thus, the design starts with single-mode, dual-mode and followed by two dual-mode resonators connected parallelly in the bandpass filter. Two dual-mode resonators connected in parallel have four orders and are spaced accordingly to generate resonance at the passband. Single-mode provides single-resonance, dual-mode provides two-resonance and two dual-mode connected in parallel provides four resonance respectively. The designed microwave filter is aimed to replace the conventional combline coaxial line filter in current base station applications with the advantage of coaxial resonator bandpass filter having an overall smaller size when compared to the conventional combline filter. The recent conventional combline filters present in base stations are relatively larger in size and expensive. Thus, the filter size and material cost can be reduced to half by having two dual-mode resonators connected in parallel to form a microwave filter. For the part of calculations, mathematical formulas are evaluated in maple software according to filter specifications given in order to build the mathematical model of the coaxial resonator bandpass filter. After the mathematical model has been completed, the microwave filter is designed and simulated in Computer Simulation Technology (CST), which is a designing platform and simulating software tool for RF applications. After obtaining the required simulation results which includes S-parameters, E-field and H-field, the designed microwave filter will be fabricated by a CNC machine. The estimated duration for this fabrication process is about one month. After the prototype has been fabricated, it will go through the process of testing and measurement via network analyzer to validate the theory by comparing the simulation results in CST with the tested results.